Strong Convergence Theorems for Quasi-Nonexpansive Mappings and Uniformly L-Lipschitzian Asymptotically Pseudo-Contractive Mappings in Banach Spaces. (12th March 2018) - Pathak, Hemant Kumar; Sahu, Vinod Kumar
ABSTRACT: A new 𝒮 -generated Ishikawa iteration with errors is proposed for a pair of quasi-nonexpansive mapping and uniformly L -Lipschitzian asymptotically pseudo-contractive mapping in real Banach spaces. We show that the proposed iterative scheme converges strongly to a common solution of quasi-nonexpansive mapping and uniformly L -Lipschitzian asymptotically pseudo-contractive mapping in real Banach spaces. A comparison table is prepared using a numeric example which shows that the proposed iterative algorithm is faster than some known iterative algorithms.